Financial Pinch Analysis: Minimum opportunity cost targeting algorithm. - Roychaudhuri, Pritam Sankar; Bandyopadhyay, Santanu (Journal of Environmental Management, 2018)
To achieve the market competitiveness as well as sustainable products and processes, a firm invests in different environmental and conservation projects. Capital budgeting essentially entails the decision of funding a set of acceptable projects from a larger pool of available projects, subject to different funding constraints. This paper proposes a new algorithm, the minimum opportunity cost targeting algorithm (MOCTA) , to address the capital budgeting problems for selecting environmental management projects. This algorithm is based on the principles of Pinch Analysis, a well-established resource conservation methodology and can be directly applied to partially acceptable projects which can be formulated as a linear programming problem. The proposed algorithm, in coordination with the branch and bound technique, can further be applied to solve mixed integer linear programming (MILP) formulation of the problem, where projects should either be completely accepted or completely rejected. A hypothetical example demonstrates the applicability of the methodology through a complex search tree. The proposed methodologies are demonstrated through a case study of selecting energy conservation projects in the Indian Paper and Pulp industry.